Proportionality in wheelchair basketball classification - Vanlandewijck, Y; Evaggelinou, C.; Daly, D.; van Houtte, S.; Verellen, J.; Aspeslagh, V.; Hendrickx, R.; Piessens, T.; Zwakhoven, B. (Adapted Physical Activity Quarterly, 2003)
The player classification system in wheelchair basketball (composed of four classes) is based on an analysis of players' functional resources through game observation and field-testing. This study examines if the classes are in the correct proportion relative to each other. During the Wheelchair Basketball World Championships in Sydney 1998, 12 teams were videotaped for three 40-min games. Eighty-eight male players were retained for a detailed performance analysis by means of the Comprehensive Basketball Grading System (CBGS). Although a slight underestimation of the functional potential of Class II and III players was noted, it was concluded that the player classification system in wheelchair basketball proportionally represents the functional potential of the players.